Ewolucja Szanghajskiej Organizacji Współpracy — od militarnego do gospodarczego wymiaru kooperacji? - Wojcieszek, Łukasz (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: Evolution of the Shanghai Cooperation Organisation — from the military to the economic cooperation The paper shows the evolution of the Shanghai Cooperation Organization (SCO), going from the military to the economic form of interaction. It describes how the Russian‑Chinese cooperation has developed over the years that have passed since the collapse of the Soviet Union as well as how the relations have gradually been tightened. The author deals with the genesis of the SCO and the multidimensional nature of its activity. Further he describes the Republics of Central Asia as an important region for Chinese economic initiatives. Due to the specific nature of the SCO, as a forum for cooperation of the two regional powers, the author presents various aspects and effects of the Russian‑Chinese cooperation. He investigates the development of the economic co‑operation as well as economic integration of the associated states. The author shows future prospects for the SCO and foreseeable trends for the development of this organization. He presents a vision of a more and more close cooperation between the post‑Soviet area with the fast growing China. Key words: military cooperation, economic cooperation, Russian‑Chinese interaction, foreseeable trends of development